ISOLATION HETEROTROPHIC BACTERIA ON SEDIMEN IN WATERS CAPE DISTRICT MEDANG NORTH RUPAT RIAU PROVINCE AND THE ACTIVITY AGAINST PATHOGENS BACTERIA (Vibrio alginolyticus, Aeromonas hydrophila and Pseudomonas sp) - Sari, Desy Mutia; Yoswaty, Dessy; ', Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Heterotrophic bacteria in marine ecosystems have important as decomposer of organic material into the elements essential. This group of bacteria can be found in a variety of habitats including marine sediment. This research aims to isolate the heterotrophic bacteria and the activity against pathogenic (Vibrio alginolyticus, Aeromonas hydrophila and Pseudomonas sp). The research was conducted from November until December 2016. Samples were obtained from the waters of Tanjung Medang, District of North Rupat, Riau Province. Isolation and antagonistic test were conducted at the Laboratory of Marine Microbiology and Biotechnology Department of Marine Sciences Faculty of Fisheries and Marine. In this research was a survey method where heterotrophic bacteria from the sediment were isolated on marine agar medium by pour plate and streak quadran techniques. Activity of the heterotrophic isolate against bacterial pathogens was conducted using diffusion agar on Mueller Hinton Agar (MHA). The number of heterotrophic bacteria ranged from 4,4 × 106 up to 13,5 × 106 CFU/g.Twelve isolates of the sediment bacteria were selected for the antagonism test. However, only nine isolates (Isolate A, C, E, F, O, S, V, W, Z) were able to inhibit the growth of pathogenic bacteria. One isolate (E) performed the highest ability to inhibit the growth of patogens (V. alginolyticus, A . hydrophila and Pseudomonas sp).Keywords: Isolation, Heterotrophic, Sediment, Antagonism, Pathogenic Bacteria.